(3TQM aUhd CHbQGWs - (3CHh GdbGSe YHO GdQMef Hf Ydj Hf CHi UGObs; (3GHbQGW GdMcjes
(3ChdgG (B:s
(3CeG HYO MeO Gddg HLejY eMGeOg , hGdKfGA Ydjg gh Cgdg , hGdUdGI Ydi QShdg eMeO GdfHi hBdg hSde hbO cGf ef GdeJbOejf hGdeJCNQjf eef JcdehG ai GdWH QChG Cf jOhfhG HYOge LedG hLhGeY ef GUhdg s
(3BNQgG (B:s
(3hCeG GdaVhd GdeOdSI hGdJi bO CYjO PcQgG HCNQI ef GdcJGH , abO JQcfG PcQgG TabI Ydi ahJ GdReGf HeGdG jLOi faYkG , hGddg JYGdi hdi GdNjQ hGdNjQI s
(3fSNI NGeSIs
(3hgj eCNhPI Yf fSNI eUhQI dPG de JXgQ HYV GdbWGJ hCWQGa GdHYV GdBNQ ef fSNI edc GdCSJGP jYbhH UQhas
(3UGMH GdebJWas
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs